2018
DOI: 10.1038/s41419-017-0218-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1253 suppresses cell proliferation and invasion of non-small-cell lung carcinoma by targeting WNT5A

Abstract: MicroRNAs (miRNA) are a class of small, noncoding RNA molecules that regulate the expression of target genes. miRNA dysregulation is involved in carcinogenesis and tumor progression. In this study, we identified microRNA-1253 (miR-1253) as being significantly down-regulated in non-small-cell lung carcinoma (NSCLC) tissues and associated with advanced clinical stage, lymph node metastasis, and poor survival. The enhanced expression of miR-1253 significantly inhibited the proliferation, migration, and invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 53 publications
3
49
0
Order By: Relevance
“…In addition, miR-1253 and RAB3D have been found to be participated in the development of human malignancies. 14,15 Thus, by investigating the effects of hsa_circ_0087862 on miR-1253/RAB3D axis, this paper further explored the potential molecular mechanisms of hsa_circ_0087862 affecting NSCLC development. As far as we know, this was the first time that hsa_circ_0087862 has been studied in detail in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-1253 and RAB3D have been found to be participated in the development of human malignancies. 14,15 Thus, by investigating the effects of hsa_circ_0087862 on miR-1253/RAB3D axis, this paper further explored the potential molecular mechanisms of hsa_circ_0087862 affecting NSCLC development. As far as we know, this was the first time that hsa_circ_0087862 has been studied in detail in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, more and more studies which focusing on the miR-24-3p expression levels with cancer progression, metastasis and prognosis of patients were carried on [4][5][6][7][14][15][16]. Thus, the exact role of miR-24-3p on the clinical prognosis of patients in various human carcinomas still need to further investigate.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a kind of endogenous non-coding RNAs of 18-22 nucleotides in length, negatively regulate target genes expression at posttranscriptional level [1][2][3]. As either oncogenes or anti-oncogenes, they are found to play vital roles in a wide range of fundamental biological processes, such as proliferation [4,5], differentiation [6,7], apoptosis [8,9], cell cycle [10][11][12][13], metastasis [14][15][16], stress response [17][18][19], metabolic [20][21][22] and etc. Owing to its detectability and stability in tissues, marrow or blood, a growing number of studies suggests that miRNAs can serve as promising biomarkers for the prognosis of carcinomas [23].…”
Section: Introductionmentioning
confidence: 99%
“…It was known the role of Wnt5a-S protein in the processes of tumor formation and growth. Liu et al positioned WNT5A as a target for miR-1253 [76]. In vitro and in vivo experiments showed that overexpression of miR-1253 significantly inhibited proliferation, migration, and invasion of NSCLC cells, while inhibition of miR-1253 had the opposite effect.…”
Section: Epigenetic Factors In the Development Of Cancermentioning
confidence: 99%